Exchange Rate Misalignment : An Application of the Behavioral Equilibrium Exchange Rate (BEER) to Botswana - Iimi, Atsushi (IMF Working Papers; Working Paper, 2006)
Botswana's successive currency devaluations and recent move from a fixed to a crawling peg exchange rate regime raise the question of whether the exchange rate might be misaligned with economic fundamentals. This paper, applying the behavioral equilibrium exchange rate (BEER) approach, analyzes the behavior of the real exchange rate for the period 1985-2004. It finds that the pula was undervalued in the later 1980s but overvalued in recent years. Some policy lessons from experiences in other countries with crawling peg arrangements are therefore considered in the context of Botswana.